Comparison of Improvement in 2-Year Survival Rate of Patients with Stage II-III Non-Small Cell Lung Cancer Treated with Different Durations of Chinese Patent Medicine: A Retrospective Cohort Study - Wang, Li; Jia, Kegang; Li, Fang; Zhang, Chenxu; Feng, Gang; Du, Jun (Frontiers in Pharmacology, 2021)
Background: Chinese patent medicine is widely used among patients with malignant tumors, and current studies have shown that long-term treatment with Chinese patent medicine is related to improved outcomes of patients. Huisheng Oral Liquid is a kind of Chinese patent medicine with the effects of curing dispersion-thirst and dissipating blood stasis. However, little is known about how it affects the survival rate of patients. Thus, patients with stage II-III NSCLC (non-small-cell lung cancer) were chosen to participate in a retrospective cohort study, which was conducted to preliminarily investigate the effects of using Chinese patent medicine and Huisheng Oral Liquid for different treatment durations on patients’ 2-year survival rate and explore the prognostic factors affecting the 2-year survival rate of those patients. Purpose: This work compares the effect of different durations of treatment with Chinese patent medicine and Huisheng Oral Liquid on the 2-year survival rate of patients with stage II-III NSCLC and explores the prognostic factors of the patients' 2-year survival rate. Methods: This retrospective cohort study included patients with non-small cell lung cancer stage II-III according to the 2015 NCCN Guidelines: Non-Small Cell Lung Cancer. The Kaplan–Meier method was used to compare the 2-year survival rate of patients treated with different durations of Chinese medicine and Huisheng Oral Liquid. The relationship between different treatment durations and degree of improvement of 2-year survival rate was explored using the Cochran–Armitage trend test. The Cox proportional-hazards regression models were used to explore factors affecting the 2-year survival rate of patients. Results: A total of 614 patients with stage II-III NSCLC diagnosed from January 2015 to December 2018 were included in this study. Patients treated with Chinese patent medicine were divided into three groups by treatment durations: < 3 months, ≥ 3 months, and ≥6 months, and those treated with Huisheng Oral Liquid were divided into < 3 months and ≥3 and ≥6 months. The results showed that ① the 2-year survival rate of patients treated with Chinese patent medicine for ≥3 months and ≥6 months was higher than that of patients treated for <3 months and the difference was statistically significant (p < 0.05). Further analysis of Huisheng Oral Liquid treatment revealed that ② the 2-year survival rate of patients treated with Huisheng Oral Liquid for ≥3 months was higher than that of patients treated for <3 months (p < 0.05). Because the total number of patients treated with Huisheng Oral Liquid for ≥6 months and the number of patients with improved outcomes were too small, there was no statistically significant difference in the 2-year survival rate between the two groups (p > 0.05). The results of the Cochran–Armitage trend test showed that the 2-year survival rate tended to increase with the duration of Huisheng Oral Liquid treatment (p < 0.05). ③ The Cox proportional -hazards regression model revealed that among all 614 patients, surgery [HR = 0.48, 95% CI = (0.34, 0.68)], chemotherapy [HR = 0.46, 95% CI = (0.31,0.67)], and treatment with Huisheng Oral Liquid for ≥3 months were protective factors [HR = 0.48, 95%CI = (0.27,0.88)], whereas male gender [HR = 1.59, 95% CI = (1.01, 2.50)] and FIB ≥4 g/L [HR = 1.95, 95% CI = (1.37, 2.77)] were risk factors. Conclusion: Chinese patent medicine treatment for ≥3 months showed an improvement in the 2-year survival rate of patients with stage II-III NSCLC. Patients treated with Huisheng Oral liquid for ≥3 months also showed an improvement in the 2-year survival rate, and the 2-year survival rate tended to increase as the treatment duration increased. Finally, male and FIB ≥ 4 g/L were risk factors for prognosis.